Mating competition among females: testing the distinction between natural and sexual selection in an insect - Varpu Pärssinen; Leigh W. Simmons; Charlotta Kvarnemo (Royal Society Open Science, 2024)
In species where females compete for mates, the male often provides the female with resources in addition to gametes. A recently suggested definition of sexual selection proposed that if females only benefit from additional resources that come with each mating and not additional gametes, female intrasexual competition for mating opportunities would result in natural selection rather than sexual selection. The nuptial gift-giving bushcricket Kawanaphila nartee has dynamic sex roles and has been a textbook example of sexual selection acting on females via mating competition. We investigated whether females of this species gain fitness benefits from nuptial gifts, additional ejaculates or both by controlling the number of matings and whether the female was allowed to consume the nutritious gift (spermatophylax) at mating. We found that egg production per day of life increased with the number of additional matings, both with and without spermatophylax consumption, but consuming the spermatophylax had an additional positive effect on the number of eggs. These effects were particularly strong in females with shorter lifespans. We discuss how the recently suggested definition of sexual selection applies to nuptial-feeding insects and conclude that both natural and sexual selections influence mating competition in K. nartee females.